Neuropeptide Y: an undisputed central simulator of avian appetite - Mahdavi , Kimia; Zendehdel, Morteza; Zarei , Hamed (Journal of Poultry Sciences and Avian Diseases, 2024)
During the last few decades, identifying the physiological pathways involved in appetite regulation has become popular among researchers. Although studying feeding regulation in birds, especially in poultries (for breeding purposes) and ornamental birds (for therapeutic purposes), is extremely important, limited experiments have been conducted on these animal models. Until today, more than fifty neurotransmitters affecting birds' appetite have been identified. In the current study, we overviewed the role of one of the most important neural mediators, neuropeptide Y (NPY), in regulating avian appetite. Based on the findings, the presence of this neuropeptide and its receptors in the key areas of food intake regulation, especially the arcuate nucleus (ARC) of the hypothalamus, has been proven. Numerous studies on birds have repeatedly shown the hyperphagic effects of NPY. Among the different NPY receptors, type 1, 2 and 5 receptors play the most important role in appetite regulation. It has also been observed that the interaction of NPY with neurotransmitters such as glucagon-like peptide-1 (GLP-1), vasotocin, bombesin, opioids, alpha-melanocyte-stimulating hormone (α-MSH), cocaine- and amphetamine-regulated transcript (CART) and gamma aminobutyric acid (GABA) is effective in NPY-induced hyperphagia. In addition, the NPY system is also involved in the effects of various mediators such as adiponectin, neuropeptide W (NPW), phoenixin-14, visfatin, adrenomedullin, spexin, kisspeptin, insulin, and somatostatin on appetite regulation. Finally, NPY seems to be one of the most important appetite-stimulating factors in birds and also plays an undeniable role in the effects of other neurotransmitters on appetite regulation.